2015
DOI: 10.3390/educsci5030199
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Elements That Support Teachers Engagement in Online Professional Development

Abstract: This study sought to identify the most effective elements required in online professional development to enable teachers to improve their use of Information and Communications Technologies (ICT) in their classrooms. Four schools in Queensland were involved, with twelve classroom teachers participating in a year-long online professional development program over the school year supported by an online mentor. The online professional development program did not provide course based or sequential learning activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 24 publications
2
29
0
4
Order By: Relevance
“…These could be individual barriers such as time, lack of skills and lack of support (Reed 2014, p. 1) or organisational ones such as departmental culture, resistance to change, funding issues or lack of management support (Glover et al 2016, p. 994 However, 'second-order' (or internal) barriers are often seen as more important - Ertmer et al theorise (2012, p. 433) that the difference between 'early adopters' and the 'early majority' is not external barriers but 'the relative weight assigned to [these]' and thus by reducing second-order barriers and increasing motivation to use TEL, teachers will find ways to overcome the first-order barriers in their settings. Kim et al (2013, p. 77) identify that persistent beliefs about current practice can act as second-order barriers and some have claimed that pedagogic change must underpin the effective introduction of TEL (Cochrane 2012;Prestridge and Tondeur 2015). However, it can be argued that increased use of TEL may in itself lead to more student-centred teaching (Howard andGigliotti 2016, p. 1362) rather than a belief that student-centred teaching is required for technology integration to take place (Kim et al 2013, p. 83).…”
Section: Barriers and Pedagogic Innovationmentioning
confidence: 99%
“…These could be individual barriers such as time, lack of skills and lack of support (Reed 2014, p. 1) or organisational ones such as departmental culture, resistance to change, funding issues or lack of management support (Glover et al 2016, p. 994 However, 'second-order' (or internal) barriers are often seen as more important - Ertmer et al theorise (2012, p. 433) that the difference between 'early adopters' and the 'early majority' is not external barriers but 'the relative weight assigned to [these]' and thus by reducing second-order barriers and increasing motivation to use TEL, teachers will find ways to overcome the first-order barriers in their settings. Kim et al (2013, p. 77) identify that persistent beliefs about current practice can act as second-order barriers and some have claimed that pedagogic change must underpin the effective introduction of TEL (Cochrane 2012;Prestridge and Tondeur 2015). However, it can be argued that increased use of TEL may in itself lead to more student-centred teaching (Howard andGigliotti 2016, p. 1362) rather than a belief that student-centred teaching is required for technology integration to take place (Kim et al 2013, p. 83).…”
Section: Barriers and Pedagogic Innovationmentioning
confidence: 99%
“…Depending on teacher experiences, professional development should focus on optimism and minimizing insecurities (Lin et al, 2015). This can be done through experience sharing seminars, verbal and written reflections, and ensuring that professional learning contexts and follow up always take place after professional training (Prestridge & Tondeur, 2015).…”
Section: /24(1)mentioning
confidence: 99%
“…As part of a research project, teachers authored weekly reflective blogs of their classroom curriculum, in addition to sharing information learned at professional conferences. 25 Similarly, reflection, engagement, and constructive dialogue were identified as benefits for continued professional development.…”
Section: Non-health Care Literaturementioning
confidence: 99%
“…4,27,30 Using a blog allows for discourse and dialogue between colleagues and educators and provides support at a peer level. 18,24,25,27 It has been suggested that contributing to a blog can facilitate the refinement of scholarly writing skills, a valuable asset for any nurse. 19,31 Finally, blogging affords nurses an opportunity to engage and connect through learning experiences.…”
Section: Advantages Of Bloggingmentioning
confidence: 99%
See 1 more Smart Citation